Late-Pregnancy Salivary Cortisol Concentrations of Ghanaian Women Participating in a Randomized Controlled Trial of Prenatal Lipid-Based Nutrient Supplements–. Issue 2 (13th January 2016) - Oaks, Brietta M; Laugero, Kevin D; Stewart, Christine P; Adu-Afarwuah, Seth; Lartey, Anna; Ashorn, Per; Vosti, Stephen A; Dewey, Kathryn G
Abstract: Background: High circulating cortisol is associated with miscarriage, preterm birth, and low birth weight. Research in nonpregnant individuals suggests that improved nutrition may lower cortisol concentrations. It is unknown whether nutritional supplementation during pregnancy lowers cortisol. Objective: Our objective was to determine whether women receiving a lipid-based nutrient supplement (LNS) throughout pregnancy would have lower salivary cortisol at 36 wk gestation compared with women receiving other nutrient supplements. Methods: We conducted a randomized controlled trial in 1320 pregnant Ghanaian women at ≤20 wk gestation who were assigned to receive daily throughout pregnancy: 1 ) 60 mg iron + 400 μg folic acid (IFA), 2 ) multiple micronutrients (MMNs), or 3 ) 20 g LNS (containing 118 kcal, 22 micronutrients, and protein). Morning salivary cortisol was collected from a subsample at baseline and at 28 and 36 wk gestation. Results: A total of 758 women had cortisol measurements at 28 or 36 wk gestation. Salivary cortisol at 36 wk gestation did not differ between groups and was (mean ± SE) 7.97 ± 0.199 in the IFA group, 7.84 ± 0.191 in the MMN group, and 7.77 ± 0.199 nmol/L in the LNS group, when adjusted for baseline cortisol, time of waking, and time between waking and saliva collection ( P = 0.67). There was an interaction between supplementation group and women's age (continuous variable, P -interaction = 0.03); and when age was dichotomized by the median, significant differences in salivary cortisol concentrations between groups were seen in women ≤26 y of age (IFA = 8.23 ± 0.284 nmol/L, MMN = 8.20 ± 0.274 nmol/L, and LNS = 7.44 ± 0.284 nmol/L; P = 0.03) but not in women >26 y old (IFA = 7.71 ± 0.281 nmol/L, MMN = 7.50 ± 0.274 nmol/L, and LNS = 8.08 ± 0.281 nmol/L; P = 0.13). Conclusions: We conclude that supplementation with LNSs or MMNs during pregnancy did not affect the cortisol concentration in the study population as a whole, in comparison with IFA, but that LNS consumption among younger women may lead to lower cortisol at 36 wk gestation. This trial was registered at clinicaltrials.gov as NCT00970866.